Analisis Kesulitan Siswa pada Materi PFB dan KPK Kelas V SDN 07 Pontianak Kota (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to identify the types of difficulties experienced by students in the material of FPB (Greatest Common Factor) and KPK (Least Common Multiple) in the fifth grade of SDN 07 Pontianak Kota. The research method used is descriptive qualitative based on the indicators of learning difficulties according to Abdurrahman (2003), which are (1) factual learning difficulties, (2) conceptual learning difficulties, (3) operational learning difficulties, and (4) principled learning difficulties. The type of research used is descriptive qualitative. This research was conducted with fifth-grade students of SDN 07 Pontianak Kota by collecting data through tests. The results revealed that difficulty learning operations is the most common type of difficulty experienced by students with a total of 53.9% of difficulty, principle learning difficulty is the second type of difficulty experienced by students with a total of 52.34% of difficulty, concept learning difficulty is the third type of learning difficulty experienced by students with a total of 48.43% of difficulty, and fact learning difficulty is the least type of difficulty experienced by students with a total difficulty percentage of 15.625%. Then the results of the study showed that students were more likely to experience difficulties in doing FPB questions than the KPK with a percentage of 67.96%.